Evolution of cell populations in vitro: peculiarities, driving forces, mechanisms and consequences - Kunakh, V.A. (Вiopolymers and Cell, 2013)
This review outlines the major features and distinctions of cell populations, types and directions of selection in such populations. Population-genetic basis for cell adaptation to growth conditions in vitro is elucidated; in particular, peculiarities of genome evolution in the course of cell dedifferentiation and further cell adaptation to growth conditions in passaged culture are evaluated. Main factors of variation and selection in cell populations in vitro, influence of growth conditions on structure of cell populations and some regularities of cultured cells and regenerated plants are considered. Details of creation of stable cell lines-producers of biologically active substances are presented. Views and suppositions of author resulting from analysis of both literature data and own multiyear studies on cell population genetics are set forth. Among others are substantiated such key statements: cell culture in vitro presents dynamically-heterogeneous biological system, clone population, which is developing (evolving) as a result of major driving factors of evolution – variation, heredity, selection and drift of genes (genotypes); interaction between these processes determines the biological characteristics of each particular cell line grown in specific conditions; in adaptation of cells to growth conditions in vitro one can single out three periods: the initial population of isolated cells, the period of strain (cell line) formation and the established strain. The division into periods is determined by the type, direction and intensity of «natural» selection that acts in cell population. The formed (adapted to growth in vitro) strains are genetically heterogeneous, they are characterized by the presence of physiological and genetic homeostasis, which are mostly caused by the action of stabilizing selection; cultured cells of higher plants are able to synthesize practically all classes of secondary (specialized) compounds (alkaloids, steroids, terpenoids, etc.); any somatic cell with living (functionally active) nucleus during its isolation and further cultivation in tissue culture, as a result of the process of «somaclonal» variability occurring according to the N. I. Vavilov’s law of homologous series in hereditary variability, can restore in it’s descendants, including regenerated plants, the entire genetic polymorphism (or at least a significant part of it) characteristic of the plant’s species and may be even it’s genus. This provides an opportunity to preserve and restore the natural polymorphism in cultured cells and tissues in vitro.